A Pathway to Preserving Malaysia’s Natural Heritage: A Case study of Politeknik METrO Betong Sarawak (PMBS) - Rehat, Clarina; Syaripuddin, Budi (Politeknik Negeri Bengkalis, 2024)
Students that are also travelers and soon to be future tourism practitioners inherit the responsibility to managing natural resources, and in order to address environmental issues, they ought to be knowledgeable andadhere to principles that are consistent with sustainable tourism. The purpose of this study is to set a standard forassessing students' perceptions on sustainable issues. 18 respondents from Politeknik METrO Betong Sarawak(PMBS) have responded to this bilingual questionnaire. The results are relatable and the findings revealed a positiveperception formed by the students on the role played by government agencies, industry players and education systemin Malaysia.